Histological Study of the Bursa of Fabricius of Broiler Chickens During Heat Stress - Tarek, Khenenou; Mohamed, Melizi; Hassina, Benzaoui; Messaouda, Ibrir (International Journal of Poultry Science, 2013)
One hundred, one day old Boiler chicks were randomly divided into two groups and kept in two rooms of different temperatures, first at a temperature of 35±2°C and the second at a temperature of 24±2°C (neutral). A samples were collected after heat exposure at 4 stages during experimental (1st, 2nd, 4th and 6 th week). Samples which were taken from the second room were served as control group. The result revealed that heat stress decreased weight of the bursa of Fabricius. Birds sacrificed at the sixth week showed a bursa with a thin parenchyma, the basal membrane hardly visible, the epithelium is folded, appearance of numerous cysts and leading subepithelial connective tissue, follicles showing lymphoid depletion and necrosis in more than 45 % of cells and moderate interfollicular fibrosis.